Iris Fulva 'Louisiana Hybrids' Louisiana Iris - Edward Gilman; Carol Lord (EDIS)
This document provides an overview of Louisiana iris hybrids, including their physical characteristics, planting requirements, and uses in landscaping. These perennials, native to Florida, feature dark green, sword-like leaves and a variety of flower colors. They thrive in USDA hardiness zones 6 through 10 and prefer acidic, moist soils but are also drought-tolerant. The document highlights their suitability for borders, mass plantings, and ground cover, noting their moderate growth rate and pest resistance. Propagation methods and planting guidelines are also discussed. Original publication date October 1999.